The Economic Consequences review of Modified Audit Reporting: Testing the Theories of Audit Assumptions - Shiva Hassanpour (Shahid Bahonar University of Kerman, 2021)
Objective: This is very important for managers and investors of the company and other stakeholders to investigate the consequences of publishing modified audit reports in Iran. There are many factors affecting the modified audit report and the purpose of this study is not to identify these factors. The results of this study can answer the question of whether in Iran the audit report and the type of auditor's opinion cause a reaction from different groups or not. Also, the role of accounting justification theories (agency hypothesis, information hypothesis and insurance hypothesis) in the economic outcome of the modified audit report was experimentally tested. Given the above, the main issue of the present study is to answer the question that what effect does the audit report and quality audit performance have on the value of the company? The purpose of this study is to identify the economic consequences of a modified audit opinion.   Methods: The research data was collected using document mining and were analyzed using a sample of 146 companies listed in Tehran Stock Exchange during the years 2007 to 2018 by Panel data and multivariate regression model.   Results: The research findings showed that the number of clauses in the audit report has an economic consequence and, consequently, reduces the sensitivity of investment expenditures to cash flows and the ratio of the tobin's Q. In addition, the role of the three theories of audit assumptions was tested according to Wallace's view. The findings show that the modified audit opinion with the criterion of the number of clauses in the condition was based on the agency theory and the information theory has economic consequences. However, according to the insurance theory, there is no economic consequence.   Conclusion: The research findind showed that modifeid audit reports has no economic consequences. The reason for rejecting this claim, which was contrary to the initial expectations of the researcher and the results of other researchers, could be the large volume of modified audit reports versus unmodified reports among the sample companies, which will cause problems in data analysis. Also, it seems that the market and the performance of shareholders do not pay much attention to the type of audit report. On the other hand, the experimental test of the economic consequences of the modified audit report was performed according to the hypotheses justifying the audit performance. The results of testing these hypotheses showed that the audited report with the criterion of the number of condition clauses, based on the assumption of agency theory and information theory has economic consequences. According to the research findings, shareholders and managers in joint stock companies operating on the Tehran Stock Exchange are advised to pay more attention to the type of audit report issued and to eliminate the clauses of the audit report and improve the reporting situation. Because a modified audit report can have negative economic consequences, so it can lead to effective measures to reduce the audit report clauses.